2020
DOI: 10.1016/j.jaci.2019.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Molecular, endoscopic, histologic, and circulating biomarker-based diagnosis of eosinophilic gastritis: Multi-site study

Abstract: Background: Eosinophilic gastritis (EG) is a clinicopathologic disorder with marked gastric eosinophilia and clinical symptoms. There is an unmet need among patients with EG for more precise diagnostic tools. Objective: We aimed to develop tissue-and blood-based diagnostic platforms for EG. Methods: Patients with EG and control subjects without EG were enrolled across 9 Consortium of Eosinophilic Gastrointestinal Disease Researchers-associated sites. An EG Diagnostic Panel (EGDP; gastric transcript subset) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…Such endoscopic abnormalities are only found with Helicobacter-associated and idiopathic LG, although idiopathic LG can mimic any of the other forms of LG. 45 The intraepithelial lymphocytosis of Helicobacter-associated LG and some idiopathic LG cases is often also visible at low power, with increased cellularity of gastric pits, very similar to the low-power changes seen in the duodenum in coeliac disease. It is usually corpus-dominant, and when there is antral involvement it is usually at least of equal severity in the antrum and corpus.…”
Section: Lymphocytic Gastritismentioning
confidence: 78%
See 3 more Smart Citations
“…Such endoscopic abnormalities are only found with Helicobacter-associated and idiopathic LG, although idiopathic LG can mimic any of the other forms of LG. 45 The intraepithelial lymphocytosis of Helicobacter-associated LG and some idiopathic LG cases is often also visible at low power, with increased cellularity of gastric pits, very similar to the low-power changes seen in the duodenum in coeliac disease. It is usually corpus-dominant, and when there is antral involvement it is usually at least of equal severity in the antrum and corpus.…”
Section: Lymphocytic Gastritismentioning
confidence: 78%
“…The inflammatory infiltrate can be band-like (mild diffuse superficial chronic gastritis), a finding that was thought to indicate H. pylori-associated gastritis, but it appears that this can also be seen in NSAID-associated LG, and in the antrum in coeliac disease. 45 Other medications, such as sartans, especially olmesartan, can produce a very similar picture ( Figure 4C-H). Checkpoint inhibitors can produce a range of changes from intraepithelial lymphocytosis to severe chronic active gastritis, or focal enhanced gastritis, and sometimes granulomas.…”
Section: Lymphocytic Gastritismentioning
confidence: 86%
See 2 more Smart Citations
“…The relative newness of EGIDs to the medical landscape speaks to the immense opportunities available that will shape the field for decades to come and that can improve the lives of patients in a relatively rapid manner. Research emanating from CEGIR2 will include further characterization of non-EoE EGID, 74 with a particular emphasis on developing consensus guidelines for these disorders, pursuing a randomized clinical trial with novel biologic therapy for EGID, and supporting innovative pilot studies. Access to CEGIR research studies can be found at the CEGIR Web site (https://www.rarediseasesnetwork.…”
Section: Future For Egidsmentioning
confidence: 99%